The Role of Artificial Intelligence (AI) in EFL Classrooms - Raungsawat, Nuntiporn; Saengroongpetch, Suwicha; Kamsuriya, Nantawan (วารสารศิลปศาสตร์ มหาวิทยาลัยธรรมศาสตร์, 2025)
This paper sheds light on integrating Artificial Intelligence (AI) in English language learning. It aims at providing definitions and characteristics of AI in educational backgrounds along with its benefits and how it has developed until recently. Moreover, AI used to encourage the English communication skills of learners is discussed. It can be clearly seen that AI is revolutionizing language education by delivering personalized, engaging, and efficient learning experiences. Utilizing computer-assisted language learning, AI enhances advancements in sizable data and natural language processing to provide tailored lesson plans, interactive practice tools, data-driven insights, and automated assessment. In addition, limitations in AI-powered tool use to develop language learning skills are stated. Research on automatic translation machines is also reviewed to demonstrate their advantages and some points that should be considered. Studies on AI conducted in Thai EFL classrooms are discussed to understand the technological trends and how AI has been implemented to support EFL education in Thailand. Besides the advantages of AI, its potential drawbacks and limitations are presented to make the article well-balanced. Finally, the paper offers innovative suggestions and implications for pedagogy with AI in the area of EFL teaching and learning.